2010
DOI: 10.1111/j.1469-8986.2009.00940.x
|View full text |Cite
|
Sign up to set email alerts
|

Is freezing an adaptive reaction to threat? Evidence from heart rate reactivity to emotional pictures in victims of war and torture

Abstract: The influence of past traumatic experiences on the defense cascade in response to affective pictures was examined in survivors of war and torture. Trauma-exposed refugees with and without Posttraumatic Stress Disorder (PTSD) as well as healthy individuals viewed 75 pictures that varied in emotional content. Heart rate (HR) was recorded during the flickering stimulation of affective pictures in the context of a steady-state experiment. Whereas healthy controls showed the typical orienting response to aversive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 30 publications
(36 reference statements)
5
48
2
2
Order By: Relevance
“…These differential correlations demonstrate the sensitivity of this technology to these constructs, while connecting them to familial PTSD symptoms in directions consistent with prior research (i.e., freezing behaviors in response to potential threat [24]; emotional dysregulation in the face of acute threat [25]).…”
Section: Discussionsupporting
confidence: 77%
“…These differential correlations demonstrate the sensitivity of this technology to these constructs, while connecting them to familial PTSD symptoms in directions consistent with prior research (i.e., freezing behaviors in response to potential threat [24]; emotional dysregulation in the face of acute threat [25]).…”
Section: Discussionsupporting
confidence: 77%
“…This enhanced fight/flight response might indicate reduced freezing as well. Also, although body sway was not assessed, the findings from Adenauer et al (37) are in line with those from Hagenaars et al (26), who found enhanced freezing in response to unpleasant pictures for healthy participants who had encountered multiple traumas but had not developed PTSD. Thus, enhanced freezing might indicate resilience.…”
Section: Introductionsupporting
confidence: 80%
“…Overall, our study demonstrates reduced freezing in PTSD measured by both its physical markers (reduced body sway and bradycardia). Together, these findings might indicate elevated fight–flight behavior and attenuated freezing in response to (laboratory) stressors (37). In addition, we replicated the HR pattern found by Hagenaars et al (14) in controls, with HR deceleration in the first half and a sustained reduced HR in the second half.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations